2017
DOI: 10.1073/pnas.1701753114
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of Saccharomyces cerevisiae DNA polymerase ε-dependent mismatch repair with purified proteins

Abstract: Mammalian and Saccharomyces cerevisiae mismatch repair (MMR) proteins catalyze two MMR reactions in vitro. In one, mispair binding by either the MutS homolog 2 (Msh2)-MutS homolog 6 (Msh6) or the Msh2-MutS homolog 3 (Msh3) stimulates 5′ to 3′ excision by exonuclease 1 (Exo1) from a single-strand break 5′ to the mispair, excising the mispair. In the other, Msh2-Msh6 or Msh2-Msh3 activate the MutL homolog 1 (Mlh1)-postmeiotic segregation 1 (Pms1) endonuclease in the presence of a mispair and a nick 3′ to the mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 57 publications
(105 reference statements)
2
33
0
Order By: Relevance
“…The 5′ nick–directed repair reactions contain ATP, Mg 2+ , WT or mutant Msh2–Msh6, replication protein A, Exo1, DNA polymerase δ, PCNA, RFC-Δ1N (RFC-Δ1N is an RFC1–5 complex containing an N-terminal truncation of RFC1 that reduces its DNA binding but leaves all other functions intact ( 59 ); the 3′ nick–directed repair assay reactions in addition contained Mlh1–Pms1. Previous studies have demonstrated that the 5′ nick–directed repair assay depends on Exo1 but does not require Mlh1–Pms1 ( 53 , 58 , 60 ), whereas the 3′ nick–directed repair assay depends on Mlh1–Pms1 ( 53 , 60 ) and under some conditions can be at least partially independent of Exo1 ( 61 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 5′ nick–directed repair reactions contain ATP, Mg 2+ , WT or mutant Msh2–Msh6, replication protein A, Exo1, DNA polymerase δ, PCNA, RFC-Δ1N (RFC-Δ1N is an RFC1–5 complex containing an N-terminal truncation of RFC1 that reduces its DNA binding but leaves all other functions intact ( 59 ); the 3′ nick–directed repair assay reactions in addition contained Mlh1–Pms1. Previous studies have demonstrated that the 5′ nick–directed repair assay depends on Exo1 but does not require Mlh1–Pms1 ( 53 , 58 , 60 ), whereas the 3′ nick–directed repair assay depends on Mlh1–Pms1 ( 53 , 60 ) and under some conditions can be at least partially independent of Exo1 ( 61 ).…”
Section: Resultsmentioning
confidence: 99%
“…In these reactions, Exo1 initiates excision at the 5′ nick in a reaction that is significantly stimulated by Msh2–Msh6 in a mispair recognition–dependent fashion resulting in excision of the mispair ( 58 , 62 ). The resulting single-stranded DNA gap is then filled in by DNA polymerase δ and accessory proteins; in addition, DNA polymerase ϵ can substitute for DNA polymerase δ ( 60 ). At concentrations of ATP (2.5 m m ) that exceed the K d for ATP binding by both the Msh2 and Msh6 nucleotide-binding sites, the Walker A Lys mutant Msh2–Msh6 complexes supported 40–75% of the level of repair supported by WT Msh2–Msh6 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Msh6 interacts with the polymerase processivity clamp PCNA (Flores-Rozas et al 2000), resulting in a fraction of Msh2-Msh6 colocalizing with the replication fork, presumably facilitating the efficient detection of DNA mismatches generated during replication (Hombauer et al 2011). Upon mismatch recognition by MSH heterodimers, MLH heterodimers (primarily Mlh1-Pms1) are recruited to the MSH-mismatch complex, which in turn recruits downstream MMR proteins such as Replication factor C (RFC), PCNA, Exo1, single-strand-binding protein RPA, DNA polymerase d and e, and DNA ligase to promote MMR through excision, resynthesis, and ligation steps [reviewed in Erie (2005, 2015), , and Bowen and Kolodner (2017)].…”
mentioning
confidence: 99%
“…Both complexes involved at least two components that were shown in our MS data to interact with CNTD1. Firstly, CNTD1 FH specifically interacts with key regulators of meiotic processes and DNA repair, particularly components of the Replication Factor C (RFC) complex, which in somatic cells acts in the 240 recruitment/activation of the DNA mismatch repair pathway 26,38,39 . CNTD1 FH also interacts with a large number of proteins belonging to the ubiquitylation pathway ( Figure S6b), including components of the SKP1-Cullin-F-Box (SCF; reviewed in 40 ), namely the E2 Conjugating enzyme CDC34 and the novel E3 ubiquitin ligase FBXW9 ( Figure S6b).…”
Section: Rfc and Scf Complexesmentioning
confidence: 99%
“…Replication factor C is a pentameric complex, consisting of RFC1 through RFC5, that loads PCNA during DNA replication 41 . RFC and PCNA have been implicated in activation of MutL endonucleases 26,38,39,42 . Our mass spectrometry data revealed CNTD1 interaction with RFC3 and RFC4 (Supplemental table 1) and was confirmed by anti-HA-immunoprecipitation 250 followed by western blot using anti-RFC3 and RFC4 antibodies ( Figure 4a).…”
Section: Replication Factor C (Rfc) Complexmentioning
confidence: 99%